Gambaran Celebrity Worship pada Penggemar Boyband Korea BTS (Army) - Wiranata, Dinar Cahya; Widya Agustin, Rin (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
Celebrity Worship is an admiration to celebrities at low to high levels that leads to pathology based on strong positive feelings but also due to poor psychological well-being. Celebrity Worship is divided into three dimensions: entertainment social value, intense personal feeling, and borderline pathological tendency. One of the celebrities being the object of celebrity worship is BTS, a boyband from South Korea. BTS fans known as ARMY come from various places, one of them in Solo Raya. Army Solo Raya is concerned about experiencing celebrity worship at a high stage and leading to pathology. Therefore, this study aims to get a quantitative picture of celebrity worship experienced by ARMY in Solo Raya. Sampling using purposive sampling with a total of 400 respondents. The scale used is a celebrity worship scale with a likert system of four answers. The existing items are declared valid because they have a score above 0.3 and declared reliable as they have an alpha Cronbach score of 0.933. Data analysis using descriptive and quantitative analysis. The result is that the celebrity worship of ARMY Solo Raya is at a high level with the most dominant social value entertainment aspect, although so the behavior of the Army Solo Raya reflects celebrity worships at all stages or aspects.